Derivación de valores económicos de la producción de leche de bovinos en el barrio el Boliche de la parroquia San Juan de Pastocalle utilizando funciones de beneficio. - Muñoz Flores, Iván Francisco (2022)
The evaluation of reproductive characteristics, considering its genotype and phenotype, helps to know the current productive state of small, medium and large dairy farms. It foresees future problems and studies the expenses, benefits, and profits that are produced per month, being a fundamental part for a breeding program and genetics. Carrying out the data collection in the Pastocalle Community in the Boliche neighborhood (this is the first step of the genetic improvement project) consisted of 133 registered animals with 35.9% of them being lactating cows, mostly of Holstein breed. Implementing the management of recorded data for each of the livestock members interested in the project consists of collecting data on the weight, feeding, health, production, reproduction, costs and benefits of production. This collection of data took place on 79 hectares of land specifically purposed for cattle feed with grasses such as alfalfa, clover and the native grass kikuyo. This feeding system “sogueo” is implemented by most farmers together with an extra feeding of by-products in order to cover all the nutritional needs for good production, growth and maintenance of each category of animals. The results obtained indicate that a lactation of 125 days in the 4 months, with an average production between 4-6 kg of milk per day, had a density of 1029-1032mg/ml at 20°C in most of the cows entering the optimal range established at the national level. Mastitis tests were carried out on each of the cows, giving a result of 65.7% in the range of Trace gave a positive result while the other remaining percent gave negative results. This generated the production of 21,360 liters of milk per day, having an average sale to dairy companies of $0.47 per liter of milk, obtaining a profit of $5,537.45 with expenses of $4,494.75 per month. These expenses consisted of 51.2% in food, 13.3% in fertilizers and rent, 5.6% in services and veterinary medicines and 29.8% in labor. A profit was obtained of $0.13 per liter of milk and a production cost of $0.34 per liter of milk. Based on the selection criteria, maintaining the density in the milk and propagating the productive characteristics of the new generations must be applied to improve milk production. Since the average of 50% of the data obtained is between 5 kg / day, with slightly positive levels of mastitis and none before the days of lactation, it should be adjusted to 305 days of the year, having a 60 day of drying season. El Boliche neighborhood is profitable in terms of milk production, maintaining quality standards, with adequate management in its feeding, using adequate values of adult bovine units per hectare of land.